Psychological and pedagogical assistance at school - between routine and reflective practice - Barbara Skałbania; Teresa Lewandowska-Kidoń (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
This article aims to highlight the reflectance as an important element of pedagogical activities, as well as the need for education of reflective practitioners, in accordance with the education law of 2012 on education standards preparing for teaching profession. Thematic considerations apply to the educational process and they are especially targeted at the area of psychological and pedagogical assistance because of its fairly marginal treatment in relation to the numerous and multi-scoped analysis of the functioning of school, especially in terms of its teaching activities.